Development of the land-based part of the detailed plan of the territory within the boundaries of the Irshan Village Council of the Korosten District of the Zhytomyr Region - Drebot, O.; Karas, I.; Khotkova, T.; Nevmerzhitska, O.; Rudenko, Yu. (Land Management, Cadastre and Land Monitoring, 2026)
The article analyzes the regulatory documents regulating the development of a detailed plan of the territory, in particular its land management part. The territory within which the research was conducted is characterized, regarding the location of land plots, their intended purpose, land categories, land rights, and the presence of restrictions on use. The research was conducted within the territory of the village of Irshansk, which mostly refers to residential and public development lands, which are characterized by an extensive network of engineering communications. It was established that within the DPT there are land plots, information about which is not entered into the database of the State Land Cadastre. Among those registered in the database of the State Land Cadastre are public use territories (streets, driveways, green zones of plantations), land plots for estate development, and areas for the construction and maintenance of commercial buildings. Based on the results of office processing of the topographic survey, the boundaries of restrictions on land use were established and shown on cartographic materials, and the areas of land plots subject to restrictions were also calculated. Among the latter: a protection zone around (along) a communication facility, protection zones around (along) an energy system facility, protection zones around engineering communications, territories in red lines; there is also a sanitary protection zone around an industrial facility; which justifies the change in the purpose of the land plot of interest and the category of land within the DPT from industrial land to residential and public development land, namely the location of a shopping center. Discrepancies were also identified in the existing state of land plots and data entered about the plots in the State Land Cadastre. In particular, the complete absence of existing restrictions in the cadastral database within the formed plots was established. Data from research materials within the DPT territory were highlighted. The scheme of work was justified on a specific example, which includes: a detailed study of current legislative and regulatory documents for the development of the DPT and the registration of its results; performing a topographic survey of the area and office processing of measurements; formation of textual and planning and cartographic materials that reflect the initial state of the research area and the results of design decisions.Received: 31.01.2026;Accepted: 17.02.2026;
Keywords: detailed plan of the territory; topographic survey; land management